Plastics Additives Database - Flick, Ernest W. (William Andrew, Inc., 2004)
Annotation The Plastics Additives Database is a unique CD-ROM containing compiled information on almost 7,000 additives from their manufacturers and distributors. From Adhesion Promoters to Waxes, this product delivers the data you need to fit your specific requirements in an easy-to-use interface. This is an efficient and effective way to path to answers. Anyone can learn to use the database within minutes. A simple four-paned window allows you to move quickly from one area to another during browsing, and a powerful search engine helps you ""mine down"" to the most specific piece of information. You can export, save, and print records as well as sort and filter like a spreadsheet. Each additive description contains properties, applications, procedures and contact information for manufacturers and distributors. The Plastics Additives Database is a single source of information needed to employ the best additives in all manufacturing situations.
Keywords: elektronické knihy; electronic books